2008
DOI: 10.1103/physrevd.78.104018
|View full text |Cite
|
Sign up to set email alerts
|

Is gravitational entropy quantized?

Abstract: In Einstein's gravity, the entropy of horizons is proportional to their area. Several arguments given in the literature suggest that, in this context, both area and entropy should be quantized with an equally spaced spectrum for large quantum numbers. But in more general theories (like, for e.g, in the black hole solutions of Gauss-Bonnet or Lanczos-Lovelock gravity) the horizon entropy is not proportional to area and the question arises as to which of the two (if at all) will have this property. We give a gen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
132
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(161 citation statements)
references
References 36 publications
29
132
0
Order By: Relevance
“…This question was addressed in ref. [24] where it was shown that in the Lanczos-Lovelock models, it is indeed the entropy that is quantized with an equidistant spectrum. This matches nicely with the fact that it is the quantity in the right hand side of Eq.…”
Section: Speculations On the Connection With The Microscopic Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…This question was addressed in ref. [24] where it was shown that in the Lanczos-Lovelock models, it is indeed the entropy that is quantized with an equidistant spectrum. This matches nicely with the fact that it is the quantity in the right hand side of Eq.…”
Section: Speculations On the Connection With The Microscopic Theorymentioning
confidence: 99%
“…We will now briefly describe this possibility, based on the results of several earlier papers, especially ref. [24]. (This is also motivated by the author's view that the currently available candidate models for quantum gravity are failures and a fresh outlook needs to be developed.)…”
Section: Speculations On the Connection With The Microscopic Theorymentioning
confidence: 99%
“…The field equations in any LanczosLovelock model, when evaluated on a static solution of the theory which has a horizon, can be expressed [30] in the form of a thermodynamic identity T dS = dE g + P dV where S is the correct Wald entropy, E g is a purely geometric expression proportional to the integral of the scalar curvature of the horizon and P dV represents the work function of the matter source. The differentials dS, dE g etc.…”
Section: Gravitational Field Equations As a Thermodynamic Identitymentioning
confidence: 99%
“…The thermodynamic extension has also been made at the apparent horizon in the braneworld cosmology [9,10,11,12]. In case of black holes horizon, the study of horizon thermodynamic has also been made by many authors (see for examples [22,23,24,25]). More recently, Cai et al [5] has shown that by employing Clausius relation, δQ = T h dS h , to the apparent horizon of a FRW universe, they are able to reproduce the modified Friedmann equations by using quantum corrected entropy-area relation.…”
Section: Introductionmentioning
confidence: 99%